Between public and private: testimonies on violence against women in state terrorism in Argentina (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
The most recent reopening of trials on crimes committed by state terrorism in Argentina have helped to expose the ways in which violence is exercised against arrested and kidnapped women, a topic that remained largely occluded for Justice and the broad public until recently. This piece is based on a larger work which analyzes some of the testi- monies of women who suffered different forms of violence especially targeted at women in clandestine detention cen- ters and legal prisons as part of the repressive system of state terrorism. These stories, a selection from more than sixty among the Oral Archive at Memoria Abierta, report and reflect on sexual and gender violence, its manifestations within the broader state terror system, its subjective impacts and echoes in the present. In this paper the focus will be on what respondents say about the places, moments and inter- locutors with whom they have been (un)able or (un)willing to refer to these experiences and their aftermath, and to their perceptions of the experience of talking it over, whether at the present hearings or at testifying in this Archive.
Keywords: Testimony; Violence against women; Lived experience; Colective memory